Thickness and Annealing Effects on Thermally Evaporated InZnO Thin Films for Gas Sensors and Blue, Green and Yellow Emissive Optical Devices - Sugumaran, Sathish; Mohd Faizal, Jamlos; Mohd Noor, Ahmad; Bellan, Chandar Shekar; Sivaraj, Manoj (Elsevier, 2016)
Indium zinc oxide (InZnO) thin films with thicknesses of 100 nm and 200 nm were deposited on glass plate by thermal evaporation technique. Fourier transform infrared spectra showed a strong metal-oxide bond. X-ray diffraction patterns revealed amorphous nature for as-deposited film whereas polycrystalline structure for annealed films. Scanning electron microscope images showed a uniform distribution of spherical shape grains. Grain size was found to be higher for 200 nm film than 100 nm film. The presence of elements (In, Zn and O) was confirmed from energy dispersive X-ray analysis. Photoluminescence study of 200 nm film showed a blue, blue-green and blue-yellow emission whereas 100 nm film showed a broad green and green-yellow emissions. Both 100 nm and 200 nm films showed good oxygen sensitivity from room temperature to 400 °C. The observed optical and sensor results indicated that the prepared InZnO films are highly potential for room temperature gas sensor and blue, green and yellow emissive opto-electronic devices